Peranan Budaya Organisasi Pada CV Nabhan Bertuah Pekanbaru - lamin lamin (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This study aims to determine the influence of organizational culture on the work discipline of CV Nabhan Bertuah employees. The sample in this study was 35 employees. Quantitative analysis includes validity and reliability tests, normality tests, hypothesis tests through t-tests and coefficient of determination (R2) analysis tests. The data analysis technique used is simple regression analysis, which serves to prove the research hypothesis. The results of the hypothesis test of this study are t count 4.121> t table 2.034 so that the results of the hypothesis test in this study are organizational culture has a significant effect on the work discipline of CV Nabhan Bertuah employees. The relationship between organizational culture and work discipline of CV Nabhan Bertuah employees is positive as evidenced by the results of the regression coefficient (b) of 0.747 which means that every increase in organizational culture by one unit will be able to increase the work discipline of CV Nabhan Bertuah employees by 0.747 units. The R Square value of 0.340 means that the contribution of organizational culture to the work discipline of CV Nabhan Bertuah employees is 34%.